Landscape of Non-canonical Cysteines in Human VH Repertoire Revealed by Immunogenetic Analysis - Ponraj Prabakaran (Cell Reports, 2020)
Summary: Human antibody repertoire data captured through next-generation sequencing (NGS) has enabled deeper insights into B cell immunogenetics and paratope diversity. By analyzing large public NGS datasets, we map the landscape of non-canonical cysteines in human variable heavy-chain domains (VHs) at the repertoire level. We identify remarkable usage of non-canonical cysteines within the heavy-chain complementarity-determining region 3 (CDR-H3) and other CDRs and framework regions. Furthermore, our study reveals the diversity and location of non-canonical cysteines and their associated motifs in human VHs, which are reminiscent of and more complex than those found in other non-human species such as chicken, camel, llama, shark, and cow. These results explain how non-canonical cysteines strategically occur in the human antibodyome to expand its paratope space. This study will guide the design of human antibodies harboring disulfide-stabilized long CDR-H3s to access difficult-to-target epitopes and influence a paradigm shift in developability involving non-canonical cysteines.